(untitled) (Revista LIDER, 2020)
This article is an analysis of state interactions related to indigenous policy in the Araucania region. This perspective is constructed through dialogue between the anthropological disciplinary perspective, in particular the “ethnography of the state” and a “Mapuche vision” based on the daily experience of one of the authors and Mapudungun language concepts. The ethnography of the state seeks to know the processes of social and cultural construction imposed on society by public policies and other actions. Specifically we are interested in approaching theses processes in the interactions produced in the implementation of social programs, as well as state actions aimed at the indigenous Mapuche population. The interactions addressed are based on the relationship established between the officer and the indigenous user, in three communities of the Araucania region. The contexts of interaction and motivation are important to decipher the impact of public policies in everyday subjects.